Multiscale Polymeric Materials for Advanced Lithium Battery Applications - Kang, Jieun; Han, Dong‐Yeob; Kim, Sungho; Ryu, Jaegeon; Park, Soojin (Advanced materials (Weinheim), 2023)
Riding on the rapid growth in electric vehicles and the stationary energy storage market, high‐energy‐density lithium‐ion batteries and next‐generation rechargeable batteries (i.e., advanced batteries) have been long‐accepted as essential building blocks for future technology reaching the specific energy density of 400 Wh kg−1 at the cell‐level. Such progress, mainly driven by the emerging electrode materials or electrolytes, necessitates the development of polymeric materials with advanced functionalities in the battery to address new challenges. Therefore, it is urgently required to understand the basic chemistry and essential research directions in polymeric materials and establish a library for the polymeric materials that enables the development of advanced batteries. Herein, based on indispensable polymeric materials in advanced high‐energy‐density lithium‐ion, lithium–sulfur, lithium‐metal, and dual‐ion battery chemistry, the key research directions of polymeric materials for achieving high‐energy‐density and safety are summarized and design strategies for further improving performance are examined. Furthermore, the challenges of polymeric materials for advanced battery technologies are discussed. Polymeric materials indispensable to building safe, high‐energy‐density advanced batteries, in terms of electrode integrity, interface stability, and extending operational limits, are reviewed. The fundamental understanding of functional polymeric materials for advanced lithium battery chemistry and key research directions are discussed, thus suggesting design strategies for polymeric materials for advanced lithium batteries with improved electrochemical performances.